Civil society institutions or semi-public agencies? State regulation of parties and voluntary organizations in Norway. Issue 4 (2nd October 2018) - Saglie, Jo; Sivesind, Karl Henrik
ABSTRACT: The relationship between the Norwegian State on the one hand, and political parties and voluntary organizations on the other, has traditionally been based on mutual trust. To assess the claim that civil society institutions are developing towards 'semi-public agencies', we review state regulation of Norwegian voluntary organizations and political parties. The State does demand more accountability and transparency in return for public funding, but many aspects are also regulated scarcely or not at all. This indicates that substantial mutual trust remains. This relationship might be characterized as a partnership based on interdependence, rather than colonization.